VULNERABLE FACTORS OF SADNESS AMONG ADOLESCENTS ININDONESIA: AN EXPLORATORY INDIGENOUS RESEARCH - Renanita, Theda; Hakim, Moh. Abdul; Yuniarti, Kwartarini W. (HUMANITAS (Jurnal Psikologi Indonesia), 2012)
Adolescence is an unstable period in humans life. Hurlock (2003)called it as the phase of storm and stress. They easily get sad and angry.Aimed of this study was to identify the causes of sadness among male andfemale adolescents in order to prevent adolescents sadness. A total numberof 412 senior high school students (males =163 and females = 249)completed open-ended questions asking about what makes them sad. Thesampling used in this research was the non-random sampling technique.Data analyzed by categorizing, open coding and cross tabulation. The resultsshowed that females feel sad when they have relationship problems (40,2%), deal with unexpected events (35, 3%), then personal problems (14,1%). Unlike female adolescents, the greatest cause of sadness for maleswas unexpected life events (42, 3%), then relationship problems (27%),and personal problems (15, 3%). This study concluded that femaleadolescents were more vulnerable towards relationship problems whichmade them sad, whilst male adolescents were more vulnerable towardlifes distress.